2023
DOI: 10.1007/s00203-023-03424-z
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of antibiotic resistomes in maize rhizospheres

Abstract: The spreading of antimicrobial resistance (AMR) in crops and food products represents a global concern.In this study, we conducted a survey of resistomes in maize rhizosphere from Michigan, California, the Netherland, and South Africa, and investigated potential associations with host bacteria and soil management practices in the crop eld. For comparison, relative abundance of antibiotic resistance genes (ARGs) is normalized to the size of individual metagenomes. Michigan maize rhizosphere metagenomes showed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…An independent study found that DfrB genes are abundant in the maize rhizosphere (microbes associated with the roots of corn), suggesting that DfrB are intrinsic to this environment. 110 Natural freshwater environments were also shown to be a major reservoir of DfrB variants. 111,112 In all these cases, DfrB were identified in environments that have presumably not been exposed to TMP such that selective pressure does not justify their presence.…”
Section: Poorly Evolved Catalysts: the Dfrb Exhibit Characteristics O...mentioning
confidence: 99%
“…An independent study found that DfrB genes are abundant in the maize rhizosphere (microbes associated with the roots of corn), suggesting that DfrB are intrinsic to this environment. 110 Natural freshwater environments were also shown to be a major reservoir of DfrB variants. 111,112 In all these cases, DfrB were identified in environments that have presumably not been exposed to TMP such that selective pressure does not justify their presence.…”
Section: Poorly Evolved Catalysts: the Dfrb Exhibit Characteristics O...mentioning
confidence: 99%